Specific features of Arabic Muslim philosophy (Journal of Philosophy Culture and Political Science, 2018)
Philosophy appeared in the Middle Ages and occupied a prominent place in the history of philosophy. Scientists wrote. that, mainly in Arabic, a group of thinkers from Muslim countries expressed themselves — the tradition of calling the philosophy doctrine in scienceThe issue of religious identity is explored.